The readable people of George Meredith - Wilt, Judith, 1941- (Princeton, New Jersey ; London, England : Princeton University Press, 1975)
Meredith's reputation as an ""unreadable"" novelist prompted Judith Wilt to examine the relationship between author and reader in Meredith's fiction-a relationship that was combative and teacherly and, she contends, a central aspect of his art. Meredith was concerned with ""readable people, "" by whom he meant his readers (as he imagined them and as they were), his characters (as he created them and as they were perceived), and himself. Focusing on Meredith's struggle to shape and change the reader, Judith Wilt examines five novels: The Ordeal of Richard Feverel, Sandra Belloni, The Egoist, On.
Acknowledgments ; Introduction; 1 The Reader and the Editor; 2 The Meredithian Subplot; 3 The Ordeal of Philosophy; 4 The Mask of Sentimentalism; 5 The Hunting of the Egoist; 6 The Making of Civilization; 7 The Survival of Romance; Conclusion; Index
Includes index.
Print version record.
JSTOR
Keywords: Meredith, George, -- 1828-1909 -- Criticism and interpretation; Meredith, George, -- 1828-1909 -- Critique et interpretation; Meredith, George, -- 1828-1909 -- Criticism and interpretation; Meredith, George, -- 1828-1909; Psychological fiction, English -- History and criticism; Characters and characteristics in literature; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh; Characters and characteristics in literature; Psychological fiction, English; Criticism, interpretation, etc